A half century of electronic fetal monitoring and bioethics: silence speaks louder than words - Sartwelle, Thomas P.; Johnston, James C.; Arda, Berna (Maternal health, neonatology and perinatology, 2017)
Bioethics abolished the prevailing Hippocratic tenet instructing physicians to make treatment decisions, replacing it with autonomy through informed consent. Informed consent allows the patient to choose treatment after options are explained by the physician. The appearance of bioethics in 1970 coincided with the introduction of electronic fetal monitoring (EFM), which evolved to become the fetal surveillance modality of choice for virtually all women in labor. Autonomy rapidly pervaded all medical procedures, but there was a clear exemption for EFM. Even today, EFM remains immune to the doctrine of informed consent despite continually mounting evidence which proves the procedure is nothing more than myth, illusion and junk science that subjects mothers and babies alike to increased risks of morbidity and mortality. And ethicists have remained utterly silent through a half century of EFM misuse. Our article explores this egregious ethical failure by reviewing EFM's lack of clinical efficacy, discussing the EFM related harm to mothers and babies, and focusing on the reasons that this obstetrical procedure eluded the revolutionary change from the Hippocratic tradition to autonomy through informed consent.